“ANÁLISIS DEL NUEVO BACHILLERATO PROPUESTO POR EL MINISTERIO DE EDUCACIÓN EN RELACIÓN CON LOS CONOCIMIENTOS PARA EL INGRESO A LAS UNIVERSIDADES EN LOS ESTUDIANTES DEL TERCER AÑO DE BACHILLERATO DEL COLEGIO TÉCNICO CAMILO GALLEGOS TOLEDO PERIODO 2012-2013”. - Once Once, Carlos Alfredo (2014)
The research was conducted in the Toledo Camilo Gallegos high school, of fhe Riobamba city, province of Chimborazo, academic year 2012-2013. Institution that is applying the guidelines of the new unified general bachelorship, its authorities, teachers and students were trained previously however, there is a great deal of uncertainty about the admission to the universities by students that are attending the third year of bachelorship, because they do not have the certainty anout the knowledge that they are being taught and it would not assure them to be prepared to enterd into the universities of this students. We did a brief analysis of the new bachelorship curriculum as well as the admission process and entry to the universities of Ecuador. Methodologically he research is based from the perpective of descriptive and explanatory study type. With the implementation of an applied research desing, its population was composed of the 92 students and 12 teachers of the third year of bachelorship. Applying data collection techniques, such as surveys of teachers and students. Obtaining that 75% of students said, teachers do not promote the development of verbal skills in classes, 66% said that they are not motivated to the numerical aptitude, and 74% were not motivated to the development of abstract reasoning, and they are the tree components to be assessed in the entrance examinations for universities. As a result the students are not prepared for this process. This had being shown in the simulator ENES in which only 15 % of the students reached a suitable score.